(untitled) (Revista de Ciências Agroveterinárias, 2004)
The maintenance of the no tillage system depends on the adequate production of matter by cover crops. The aim of this study was to evaluate the accumulation of matter in aboveground cover crops, under monocropping and intercropping systems. The experiment was carried out in Canoinhas, SC, Brazil, from June to October of 2003. In the 45, 60, 75, 90, 105 and 135 days after the sowing (DAS) was evaluated the accumulation of dry and fresh matter, dry matter content and soil covering to the subsequent crops: black oat (Avena strigosa Schieb), ryegrass (Lolium multiflorum Lam.), rye (Secale cereale L.), Raphanus sativus L., black oat + vetch (Vicia sativa L.) intercropping and the five species sowed in intercropping. There were significative interaction between crops and valuation time in all variables. The intercropping systems showed the best production of dry and fresh matter on 135 DAS. The Raphanus sativus L. showed high speed fresh and dry matter accumulation, moreover soil covering quickness. On the other hand, the ryegrass showed low velocity of matter accumulation.